CASH FLOW ANALYSIS OF SHARIA FINANCIAL STATEMENTS IN SHARIA FINANCIAL INSTITUTIONS - Malik, Rizki Azizah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
Healthy Islamic financial institutions can be identified through financial reports that are accurately prepared, processed, and presented by an organization with accountability, one of which is the Cash Flow report. The aim of this scientific paper is, firstly, examine cash flow from operational activities. Secondly, from investment activities. Thirdly,  from funding activities. Fourthly, analyze impact of sharia on cash flow. Lastly, analyze how zakat affects cash flow of Islamic Financial Institutions (IFI). This research employs library research approach. The findings indicate that cash flow from operating activities part of cash flow statement that showcases cash transactions contributing net income. Cash flow from investing activities involves cash movements related to purchase, sale of long-term assets and other non-cash equivalents. Cash flow from financing activities reflects cash inflows from the issuance equity, debt securities, dividend disbursements, repurchase equity, and repayments debt securities.  Zakat mechanisms can utilized support social initiatives and improve infrastructure. Islamic Financial Institutions required fulfill their zakat obligations, which reflected in their cash flow reports. The study revealed that the application of Shariah principles in Islamic financial reporting can enhance consumer confidence, the integrity of financial institutions, and contribute to national and global economic development.